Bandwidth Enhancement on Microstrip Antenna with Dual Feed Line and Truncated for 5G Applications - Marnel, Sonfia Putra; Astuti, Dian Widi; Alaydrus, Mudrik; Majid, Huda A (Universitas Syiah Kuala, 2025)
The microstrip antenna is low-profile, meaning it has a narrow bandwidth. Additionally, the microstrip antenna is compact, making it highly suitable for implementation in small devices. Its low-profile nature is due to its thin thickness and flexibility, allowing it to be applied on curved surfaces. Technology 5G operating at the 3.5 GHz frequency requires a minimum bandwidth of 100 MHz to support high-speed data transmission and large network capacity, in accordance with the standards set by 3GPP and ITU. This study explores the combination of dual-feed and truncated methods to broaden the antenna's bandwidth. Truncation on the patch helps expand the bandwidth by altering the current distribution on the patch, which can affect the antenna's resonance. The antenna design is carried out using High-Frequency Structure Simulator (HFSS) software. This study shows the optimal bandwidth based on previous references, bandwidth alignment within the frequency range of 3.44 to 3.62 GHz with a simulated bandwidth of 180 MHz, and a measured bandwidth of 210 MHz within the frequency range of 3.42 GHz to 3.62 GHz.